Effects of rituximab treatment on the serum concentrations of vitamin D and interleukins 2, 6, 7, and 10 in patients with rheumatoid arthritis - Hasan E (Dove Medical Press, 2012)
Eman Hasan1, Samuel Olusi2, Adel Al-Awadhi3, Khalid Mokaddem1, Prem Sharma4, Sunila George21Rheumatic Disease Unit, Al-Amiri Hospital, Ministry of Health, Kuwait; 2Department of Pathology, Faculty of Medicine, Kuwait University, Kuwait; 3Department of Medicine, Faculty of Medicine, Kuwait University, Kuwait; 4Computer Unit, Health Sciences Center, Kuwait University, KuwaitBackground: Rituximab, a monoclonal antibody that selectively targets CD20-positive B-lymphocytes, is used for the treatment of patients with rheumatoid arthritis (RA) with an inadequate response or tolerance to tumor necrosis factor inhibitors. The objective of this study was to investigate the effects of rituximab treatment on the serum concentrations of vitamin D, interleukin (IL) 2, IL-6, IL-7, and IL-10 in patients with rheumatoid arthritis (RA).Methods: Forty-five patients, aged 25–78 years, were enrolled into a cohort prospective study. All patients were treated with intravenous rituximab. Disease activity score-28 (DAS-28) and serum concentrations of rheumatoid factor (RF), C-reactive protein (CRP), anticyclic citrullinated peptide (anti-CCP), erythrocyte sedimentation rate (ESR), health assessment questionnaire (HAQ), vitamin D, ILs 2, 6, 7, and 10 were estimated in the patients before and after treatment with rituximab.Results: DAS-28, HAQ score, and serum concentrations of CRP, RF, anti-CCP, IL-2, IL-6, IL-7, IL-10, and ESR significantly decreased after treatment. All 45 patients had vitamin D deficiency before treatment and this did not significantly change after treatment. However no significant association was found among serum vitamin D concentration and any of the ILs.Conclusion: We concluded from this study that although rituximab treatment of patients with RA significantly reduced their disease activity and serum concentrations of IL-2, IL-6, IL-7, and IL-10, it did not significantly alter their vitamin D status. Furthermore, no significant association was found among serum vitamin D concentration and any of the ILs.Keywords: vitamin D, rituximab treatment, rheumatoid arthritis, interleukins